Hepatic mucormycosis mimicking hilar cholangiocarcinoma: A case report and literature review - Li, Ke-Wei (Baishideng, 2010)
Mucormycosis is a rare but invasive opportunistic fungal infection associated with a high mortality rate, and normally occurs in immunocompromised patients. In this report, we describe an immunocompetent patient suffering from hepatic mucormycosis secondary to adrenal mucormycosis, which masquerades as hilar cholangiocarcinoma. After surgical procedure and treatment with amphotericin B and itraconazole, the patient recovered well and had a 2-year infection-free survival. To our knowledge, this special clinical manifestation of hepatic infection as well as adrenal mucormycosis has not been reported to date. Meanwhile, this is the first case of an immunocompetent patient with both adrenal and hepatic mucormycosis who has been treated successfully.